(untitled) (Research, Society and Development, 2021)
The objective was to analyze the process of land use and occupation in the municipality of Novo Progresso in the State of Pará, linking it with the most economically important activities developed in this region. The limit shapefile of the municipality of Novo Progresso was used on the Google Earth Engine (GEE) online platform, which provided a mosaic of orbital images, from the Landsat-8 / OLI-TIRS satellite, for the year 2019. The classification process was made from the GEE Code Editor, using a spectral index of vegetation to aid classification (Normalized Difference Vegetation Index - NDVI). Software QGis 3.10.6 was used to prepare maps of the municipality’s location and the land use and land cover classification maps. The data were tabulated in spreadsheets to determine the growth rates of the analyzed period. In order to assess the reliability of the classification, the Global Accuracy method and the Kappa Index were used. It was possible to identify that in 2019, there was an incidence of 3,064,396.65 ha (80.3%) of dense forest, an area of ​​496,104.07 ha (13.0%) with exposed soil, 248,052.03 ha (6.5%) of secondary forest, and only 7,632.37 ha (0.2%) with predominance of hydrography, totaling an area of 3,816,185.13 ha. The areas that are exposed to the exposed soil are not directly related to population growth, but rather to the way in which land use is established, based on the main activities developed in the region considering that the productive logic occurs in a disordered way, not respecting the criteria of sustainable development.